2005
DOI: 10.22358/jafs/70515/2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected rumen fauna on the digestion of starch and outflow of α-glucose polymers from the reticulo-rumen of sheep

Abstract: The role of rumen ciliates in starch digestion is not well known. The objective of this study was to examine the influence of the ciliates Eudiplodinium maggii and Entodinium caudatum on the turnover of dietary starch in the rumen. It was found that ciliates significantly increased the contents of α-D-glucose polymers in the rumen and their amount passing to the omasum (P<0.05). Competition among the ciliate species for starch was also observed. It is concluded that the effect of ciliates on the metabolism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
2
2
0
Order By: Relevance
“…In our study, we observed a decrease the amylolytic specific catalytic activity only in the group with inorganic Mn in comparison to the control group. The results are consistent with other studies in which a negative impact of ciliates on rumen amylolytic bacteria was found [ 44 , 45 ]. CMC-ase specific activity was increased by both Mn supplements in comparison to control group.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we observed a decrease the amylolytic specific catalytic activity only in the group with inorganic Mn in comparison to the control group. The results are consistent with other studies in which a negative impact of ciliates on rumen amylolytic bacteria was found [ 44 , 45 ]. CMC-ase specific activity was increased by both Mn supplements in comparison to control group.…”
Section: Discussionsupporting
confidence: 93%
“…The results show that the establishment of ciliates in the rumen increased the rumen fluid volume by about 18%. These results are consistent with previous studies by Bełżecki and Michałowski (2005). They disagree, however, with the findings of Orpin and Letcher (1984), who observed an increase in the rumen fluid volume following defaunation of sheep.…”
Section: Resultssupporting
confidence: 83%
“…The decrease of rumen protozoa in the inhibitor treatments corresponded with increase of amylolytic and saccharolytic bacteria, such as Treponema , Streptococcus , and Succinivibrio , all of which are known sugar-fermenting bacteria in the rumen (Stanton and Canale-Parola, 1980; Patterson and Hespell, 1985; O’Herrin and Kenealy, 1993; Nagaraja, 2016). The negative correlation between rumen protozoa and amylolytic bacteria has been previously noted (Arakaki et al, 1994; Bełżecki and Michałowski, 2005), and the increase of these bacteria could be attributed to the decreased predation and the lack of competition for starch from rumen protozoa (Eadie and Mann, 1970; Kurihara et al, 1978).…”
Section: Discussionmentioning
confidence: 58%